Cold argon plasma-induced aggregated and non-aggregated structural changes in casein and peptidomic insights into allergenicity - Cai, Ruiyi; Tan, Chin-Ping; Lai, Oi-Ming; Dang, Yali; Liu, Aiming; Choeng, Ling-zhi; Pan, Daodong; Du, Lihui (Elsevier Ltd, 2025)
Casein (CN) is a common allergen that is challenging to avoid in modern foods. The effect of cold argon plasma (CAP) on reducing CN antigenicity was investigated, focusing on alterations in epitope structure and sequence. CAP mainly contains hydroxyl radicals (∙OH). After a 12-min CAP treatment, the result of ELISA demonstrated an 80.46 % reduction in antigenicity. Transmission electron microscopy and electrophoresis revealed that certain CN aggregated, while multispectral analysis indicated that part of CN was fragmented into smaller peptides. The predictive 3D model suggested the disruption of linear epitopes located in the α-helix region might contribute to the reduced allergenicity. The peptide sequences were compared to the linear epitopes predicted by immunoinformatics approaches, revealing some reduction or breakage of key allergic sequences. Meanwhile, amino acids with aromatic side chains and hydrophobic groups were susceptible to CAP-induced modifications. This investigation demonstrated CAP could be beneficial for processing hypoallergenic foods.